(untitled) (Balthazar, 2025)
This article examines the tension between political obligation and personal loyalty in the context of exile, drawing on the theories of Judith Shklar and utilizing Hisham Matar’s literary work, My Friends (2023), as a primary analytical framework. Through an interdisciplinary investigation that interweaves political philosophy, history, and literature, the work examines how exile compels individuals to confront complex moral dilemmas, thereby questioning their relationships with the state, the community, and themselves. The examples presented in the essay provide a contemporary, narrative perspective on the fragmented identity of exile. The essay highlights how Shklar’s thought, centred on the relationship between rationality and affectivity, offers crucial tools for interpreting the ethical and political challenges that characterize the experience of exile. At the same time, Matar’s work enriches this analysis, highlighting the personal and psychological implications of these dynamics. In conclusion, the article proposes that exile not only represents a condition of loss but also an opportunity to question the meaning of identity, loyalty and belonging in a globalized and fragmented world.